Gestión y Desarrollo de Empresas Innovadoras - Frick, Alexis Maximiliano; Frick, Silvia Teresa Ferreira de (Journal of Technology Management & Innovation, 2013)
The New Technology-Based Firms (NTBFs) represent, for its flexibility and organizational and business capacity, a source of innovation that leverages the local development potentials in which they are found. However, the difficulties such enterprises have to confront if they want to be inserted in a competitive market can become barriers to its development. The NTBFs success is strongly influenced by the management model in place since the start of its activities, even before the legal incorporation of the company. This paper presents a method of NTBFs management and development based on a methodology called CEC (Collaborative Venture Capital) developed by a group of angel investors acting since 2008 in Brazil. For illustrative purposes, we analyze the case of a successful startup, supported by that group.